Tyrosol Facilitates Neovascularization by Enhancing Skeletal Muscle Cells Viability and Paracrine Function in Diabetic Hindlimb Ischemia Mice - Jianqi Zhang; Jianqi Zhang; Dyah Ari Nugrahaningrum; Dyah Ari Nugrahaningrum; Olivia Marcelina; Olivia Marcelina; Agnes Dwi Ariyanti; Agnes Dwi Ariyanti; Guixue Wang; Guixue Wang; Caiping Liu; Caiping Liu; et al. (Frontiers Media S.A., 2019)
As one of the most severe manifestations of diabetes, vascular complications are the main causes of diabetes-related morbidity and mortality. Hyperglycemia induces systemic abnormalities, including impaired angiogenesis, causing diabetic patients to be highly susceptible in suffering hindlimb ischemia (HLI). Despite its severe prognosis, there is currently no effective treatment for diabetic HLI. Skeletal muscle cells secrete multiple angiogenic factors, hence, recently are reported to be critical for angiogenesis; however, hyperglycemia disrupted the paracrine function in skeletal muscle cells, leading to the impaired angiogenesis potential observed in diabetic patients. The present study showed that tyrosol, a phenylethanoid compound, suppresses accumulation of intracellular reactive oxygen species (ROS) caused by hyperglycemia, most plausibly by promoting heme oxygenase-1 (HO-1) expression in skeletal muscle cells. Consequently, tyrosol exerts cytoprotective function against hyperglycemia-induced oxidative stress in skeletal muscle cells, increases their proliferation vigorously, and simultaneously suppresses apoptosis. Furthermore, tyrosol grossly increases the secretion of vascular endothelial growth factor-A (VEGF-A) and platelet-derived growth factor-BB (PDGF-BB) from skeletal muscle cells. This leads to enhanced proliferation and migration capabilities of vascular endothelial and smooth muscle cells, two types of cells that are responsible in forming blood vessels, through cell-cell communication. Finally, in vivo experiment using the diabetic HLI mouse model showed that tyrosol injection into the gastrocnemius muscle of the ischemic hindlimb significantly enhances the formation of functional blood vessels and subsequently leads to significant recovery of blood perfusion. Overall, our findings highlight the potential of the pharmacological application of tyrosol as a small molecule drug for therapeutic angiogenesis in diabetic HLI patients.